Effect of the seed extract of Carica papaya L. (Caricaceae) on Spodoptera frugiperda Smith - Ramos Otiniano, Cynthia Catheryne; Programa de Estudio de Medicina Humana, Universidad Privada Antenor Orrego, Trujillo, PERÚ (2023)
The Spodoptera frugiperda larvae are highly damaging to different crops. Its eradication requires the use of different compounds including secondary metabolites. Therefore, this research was performed to evaluate the biocidal effect of the ethanolic extract of Carica papaya (Caricaceae) seed on larvae of stage I of S. frugiperda. The larvae of S. frugiperda in stage I were treated with de 10%, 15% y 20% of aqueous solutions and evaluated at 15, 30, 45, 60, 75 and 90 minutes. It was found that the mortality of S. frugiperda larvae varied under different concentrations of C. papaya seed extracts. The 15 and 20% concentrations exhibited a higher biocidal effect with 65 and 100% mortality. The 10% C. papaya concentration showed a mortality of 40% on stage I larvae of S. frugiperda. Moreover, mortality rates of 100% were obtained after 60 minutes when larvae were exposed to the 20% ethanolic extract of C. papaya seeds. Therefore, it is concluded that the ethanolic extract of C. papaya seeds has a biocidal effect on S. frugiperda larvae.